(Re)inventions of political prisoners in a prison of military dictatorship - Farias, José Airton de (Em Perspectiva, 2017)
In Ceará, after the defeat of the armed left, the military dictatorship kept prisoners of revolutionary militants in the Paulo Sarasate Penal Institute (IPPS). There, political prisoners developed new practices, opening gaps in the dictatorship's prison structure and developing practices, tactics and strategies, carried out reconstructions and resignifications, all of relief for the redefinition of their identities and political projects. In this process, often, elements of the communist political culture were present. The article focuses on the resignifications made by prisoners in some prison environments and how this process impacted on their personal and political trajectories: the kitchen, the cells themselves, the workshops. It is also attentive to the artisan's artistic and artistic production and its different meanings.